Digital marketing communication strategies in micro social enterprises - Hollen, Chinara (2018)
Micro social enterprises play an important role in our society. Therefore, understanding how they utilize digital marketing in today’s highly competitive environment becomes vital. The author wanted to fill the gap in the current research on micro social enterprises and their digital marketing (Gogula, 2014; Shaw, 2004; Mitchell, Madill & Chreim, 2014; Sim, 2015) by conducting a qualitative research. The aim of the research was to understand the digital marketing strategies of micro social enterprises in Finland as well as shedding light on the factors affecting the adaptation of digital marketing strategies among the case companies. In order to find answers to the research questions, the author chose to interview seven micro social enterprises that bear the Social Enterprise Mark in Finland. The mark was chosen as a selecting factor as it provides the social enterprises that fit the characteristics chosen by the study. The detailed description of the case companies was included to allow the reader to understand what types of micro social enterprises were investigated. The main findings of the study reveal that the case companies utilize various digital marketing communication tools and the degree of utilization of digital marketing activities varies among the case companies. Some case companies prefer one digital marketing communication tool to another contingent on their product/service, target customer and goals. The study revealed different objectives of online marketing among the case companies with brand building, raising awareness and communication of social cause being most prominent ones. The utilization of online marketing among the case companies depended on the resource-related, owner-manager, and environmental factors. Resource-related constraints were found to be the prevailing reason for the case companies that obstruct the greater adaptation of digital marketing. Being micro social enterprises with the goal of promoting social cause rather than making profits, the case companies were bootstrapped and could not invest a lot of resources into marketing. Owner-manger factors and environmental factors had also an effect on utilization of online marketing practices, with the former being more important than the latter. The results of the findings also show that the case companies did not have consistent digital marketing strategies, content marketing strategies and did not utilize analytics regularly. The reasons for that were also linked to resource-related factors.